Thematic review on counseling crisis and intervention in school - Ismail, Yusnizal; Zakaria, Noor Syamilah; Puad Kari, Dharatun Nissa (Malque Publishing, 2024)
Crisis counseling and intervention in schools play a crucial role in addressing students' psychological needs during crisis, yet there is limited comprehensive literature reviewing their application and effectiveness.This thematic review synthesizes research on crisis counseling and intervention in schools, descriptions, and evaluations. A systematic search was conducted using the Scopus and Web of Science databases to identify relevant studies published between 2019 and 2023. A total of 25 studies were selected based on predefined inclusion criteria and were analyzed to extract key themes related to crisis counseling and intervention in schools. Three primary themes emerged from the analysis: (1) the roles of school counselors, (2) crisis preparedness, and (3) crisis intervention strategies. These themes were explored in relation to various methodologies used in the studies, highlighting multiple approaches counselors use to integrate crisis counseling knowledge for prevention and intervention within school settings. The review underscores the importance of school counselors' roles in crisis preparedness and intervention. However, further empirical research is needed to support and expand upon current recommendations, ensuring more effective crisis counseling practices in schools.